ANALISIS PERBANDINGAN PENGGUNAAN ENERGI LISTRIK KWH PRABAYAR DAN KWH PASCABAYAR DI DESA MBAWA KABUPATEN BIMA - Suaedin Indra Permatu Adi; Muhammad Hidayatullah; Paris Ali Topan; Nova Aryanto (Program Studi Teknik Elektro, 2023)
The purpose of this study was to determine the comparison of cost and usage differences between prepaid kWh and postpaid kWh. This research was conducted in Mbawa Village. Data collection in this study was carried out observation and interviews to prepaid and postpaid consumers. The number of respondents interviewed in this study were 20 respondents of prepaid and postpaid kWh users, including 10 respondents of 1300 VA postpaid kWh users and 10 respondents of 1300 VA prepaid kWh users. The method used in the research is mixed method. The results obtained after this study are that there is no significant cost difference in the results of hypothesis testing between prepaid and postpaid consumers of 1300 VA power because in hypothesis testing using a significant level value of 0.05 shows that the test results of a significant value> 0.05, namely 0.060. Based on the results of the calculation, there is a difference in the use of household electrical equipment power using kWh prepaid and postpaid 1300 VA power where the average power usage of prepaid consumer electrical equipment is 1567 Watts and in postpaid consumers with an average usage of electric power of 1603 Watts.